Meta analisis kemampuan pemecahan masalah matematis siswa pada implementasi contextual teaching and learning (CTL) - Khoirunnisa, Farah Dina; Iwan Junaedi; Iqbal Kharisudin; Scolastika Mariani; Arief Agoestanto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
The purpose of this study is to review the improvement of students' mathematical problem solving skills in the implementation of Contextual Teaching and Learning (CTL) from several articles in previous studies comprehensively and in depth in various schools, materials, or classes. This research method uses meta-analysis which consists of five stages, namely the definition of the research problem, data collection, coding process, statistical analysis, and presentation of results.. Based on the results of the study, it is obtained that the effect size value is included in the three categories of medium, large, and very large which means that the increase in mathematical problem solving ability on the implementation of Contextual Teaching and Learning (CTL) and the results of the calculation of the two means test can be found that then  is rejected which means that the average experimental group is better than the control group. Thus, there is an increase in students' mathematical problem solving ability in the implementation of Contextual Teaching and Learning (CTL).